1997
DOI: 10.1042/bj3270585
|View full text |Cite
|
Sign up to set email alerts
|

Expression of placental alkaline phosphatase does not correlate with IgG binding, internalization and transcytosis

Abstract: The human homologue of FcRn, an IgG Fc receptor expressed in rat villous syncytiotrophoblasts, might be involved in IgG transfer from the maternal to the fetal circulation. However, because the receptor does not bind IgG at the physiological pH of the maternal blood (pH 7.4), FcRn is probably not involved in the initial uptake of IgG. A role in IgG internalization has been suggested for placental alkaline phosphatase (PLAP), which is highly expressed on the apical surface of syncytiotrophoblasts. To determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 59 publications
(85 reference statements)
1
17
0
Order By: Relevance
“…In view of these two findings, direct binding of IgG at the microvillous surface to FcRn can hardly explain uptake of IgG by the STB (Story et al, 1994). Since no direct evidence for binding of IgG to other proteins expressed in the microvillous surface like annexin II or placental alkaline phosphatase as intermediary carriers could be demonstrated (Stefaner et al, 1997;Simister and Story, 1997), it was postulated (Israel et al, 1995), that similar to the rodent yolk sac endoderm IgG in the syncytial layer internalizes nonspecifically by fluidphase endocytosis and after reaching an acidified endosomal compartment binds to FcRn (Roberts et al, 1990). As shown recently by analyzing mice fetuses resulting from matings of FcRN +/-parents, it was found that FcRN -/-fetuses contained negligible amounts of IgG.…”
Section: Syncytiotrophoblast (Stb)mentioning
confidence: 99%
“…In view of these two findings, direct binding of IgG at the microvillous surface to FcRn can hardly explain uptake of IgG by the STB (Story et al, 1994). Since no direct evidence for binding of IgG to other proteins expressed in the microvillous surface like annexin II or placental alkaline phosphatase as intermediary carriers could be demonstrated (Stefaner et al, 1997;Simister and Story, 1997), it was postulated (Israel et al, 1995), that similar to the rodent yolk sac endoderm IgG in the syncytial layer internalizes nonspecifically by fluidphase endocytosis and after reaching an acidified endosomal compartment binds to FcRn (Roberts et al, 1990). As shown recently by analyzing mice fetuses resulting from matings of FcRN +/-parents, it was found that FcRN -/-fetuses contained negligible amounts of IgG.…”
Section: Syncytiotrophoblast (Stb)mentioning
confidence: 99%
“…In rat hepatocytes, internalization below 207C leads to accumulation of ASGP in early, receptor-positive endosomes, thereby inhibiting delivery to late endosomes and lysosomes [9,28]. Upon internalization at 167C transcytosis of anti-SC antibodies -that label the pIgA pathway -are accumulated in early endosomes leading to complete inhibition of antibody secretion into bile [29]. Finally, recycling of transferrin in the isolated perfused rat liver is largely reduced but not completely blocked when internalization is carried out at 167C.…”
Section: Introductionmentioning
confidence: 99%
“…The protein that has many allelic variants binds IgG with a low affinity of about 3 × 10 5 M -1 (2). It was supposed to function in the endocytosis of IgG at physiological pH of the maternal blood (2,78). However, experiments with carcinoma cell lines transfected with the PLAP cDNA do not support this assumption (78).…”
Section: Placental Alkaline Phosphatase (Plap) and Annexin IImentioning
confidence: 71%
“…It was supposed to function in the endocytosis of IgG at physiological pH of the maternal blood (2,78). However, experiments with carcinoma cell lines transfected with the PLAP cDNA do not support this assumption (78). Another placental protein is the 40 kDa Annexin II found in abundance in the trophoblast and endothelial cells of the placenta (2,79).…”
Section: Placental Alkaline Phosphatase (Plap) and Annexin IImentioning
confidence: 98%
See 1 more Smart Citation